Amorphous nanocatalyst, preparation method and application thereof
The preparation of amorphous nanospherical NiWO4 catalyst by co-precipitation method solves the problem of low urea electrooxidation activity, significantly improves the power density of direct urea fuel cells, and simplifies the preparation process.
Patent Information
- Application Number
- CN202210045536.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-01-15
AI Technical Summary
The prior art has low urea electrooxidation activity when treating urea wastewater, resulting in low power density of direct urea fuel cells, limiting their application.
A preparation method of amorphous nanocatalyst is adopted to synthesize nanosphere NiWO4 catalyst by co-precipitation method. The surface is rich in Ni and has good electrochemical catalytic oxidation of urea.
The electrooxidation activity of urea is improved, more NiOOH active sites are generated, and the power density of direct urea fuel cells is significantly improved, the preparation process is simplified and the cost is reduced.
Smart Images

Figure CN116477669B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano catalysts, in particular to an amorphous nano catalyst, a preparation method and application thereof. Background Art
[0002] Urea (CO(NH2)2) is widely used as a fertilizer and produces urea-rich wastewater. In addition, urea is also the main component of human and animal urine. A large amount of untreated urea-containing wastewater will naturally convert into ammonia, which will be oxidized into environmental pollutants such as nitrite, nitrate and nitric oxide. Traditional treatment methods for urea-containing wastewater, such as biological decomposition, chemical oxidation and thermal hydrolysis, are not only energy-consuming, but also technically expensive and inefficient. Therefore, the management and treatment of urea has become an important energy and environmental issue. Urea is regarded as a hydrogen carrier for long-term sustainable energy supply due to its stability, relative non-toxicity, non-flammability, easy storage and transportation. Direct urea fuel cell is a promising energy sustainable development approach that can treat urea-rich wastewater while generating electricity to produce clean products N2, CO2 and H2O. However, the slow rate of urea electrocatalytic oxidation reaction leads to low power density, which seriously affects its application. The high generation potential and few exposed active sites of NiOOH, the active component of urea electrooxidation, lead to its low catalytic activity, which limits the application of direct urea fuel cells. Therefore, it is urgent to develop a high-performance electrocatalyst that promotes the generation of NiOOH active sites to improve the urea electrooxidation activity.
[0003] In order to improve the urea electrooxidation activity, people have invested a lot of effort in the design of non-precious nickel-based electrocatalysts for urea electrooxidation, but their catalytic performance is not particularly satisfactory and the preparation process is complicated. Therefore, the development of nanocatalysts with rich and uniform active sites, simple synthesis methods, and strong activity is an urgent requirement for urea electrooxidation. Summary of the invention
[0004] The purpose of the present invention is to overcome the disadvantages of the prior art and provide an amorphous nanocatalyst, a preparation method and application thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing an amorphous nanocatalyst comprises the following steps:
[0007] (1) preparing Ni(NO3)2 aqueous solution and Na2WO4 aqueous solution;
[0008] (2) adding the Na2WO4 aqueous solution dropwise into the Ni(NO3)2 aqueous solution with stirring to obtain a suspension;
[0009] (3) continuously stirring the suspension, and then allowing it to stand to obtain a precipitate;
[0010] (4) Washing the precipitate and then drying it to obtain an amorphous nanocatalyst.
[0011] Furthermore, in the Ni(NO3)2 aqueous solution in step (1), 0.004 to 0.005 mol Ni(NO3)2·6H2O is dissolved in every 30 mL of deionized water.
[0012] Furthermore, in the Na2WO4 aqueous solution in step (1), 0.004 to 0.005 mol Na2WO4 is dissolved in every 30 mL of deionized water.
[0013] Furthermore, in step (2), the molar ratio of Ni to W in the suspension is (0.8-1.25):1.
[0014] Furthermore, the drying temperature in step (4) is 70°C.
[0015] An amorphous nano catalyst is obtained according to the preparation method of the present invention.
[0016] A non-crystalline nanocatalyst in the form of nanospheres.
[0017] The application of the amorphous nanocatalyst of the present invention is used for electrocatalytic oxidation of urea.
[0018] The amorphous nano catalyst of the present invention is used as an anode catalyst of a direct urea fuel cell.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The amorphous nanocatalyst and preparation method thereof of the present invention adopt a simple one-step coprecipitation method to synthesize the amorphous nanocatalyst, which has a simple process and low cost. The surface of the prepared nanocatalyst is rich in Ni and has good performance of electrochemical catalytic oxidation of urea.
[0021] Furthermore, Na2WO4 and Ni(NO3)2 were used as raw materials, and the chemical reagents used were all of analytical grade and could be used directly without further purification.
[0022] The amorphous nanocatalyst of the present invention is used for electrocatalytic oxidation of urea, can generate more NiOOH active sites, and has higher urea electrooxidation activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The SEM image and EDX image of the amorphous nanocatalyst prepared in Example 1;
[0024] Figure 2 XRD diagrams of the products prepared in Example 1 and Comparative Examples 1-3;
[0025] Figure 3 HRTEM and SAED images of the amorphous nanocatalyst prepared in Example 1;
[0026] Figure 4 The amorphous nanocatalyst of Example 1 and the crystalline NiWO4 electrode of Comparative Example 2 were tested in 1M KOH at 10 mV·s -1 Electrochemical performance diagram at scanning rate;
[0027] Figure 5 The amorphous nanocatalyst of Example 1 and the crystalline NiWO4 electrode of Comparative Example 2 were tested in 1M KOH+0.33M urea at 10mV·s -1 Electrochemical performance diagram at scanning rate;
[0028] Figure 6 is a schematic diagram of the structure of a direct urea-hydrogen peroxide fuel cell;
[0029] Figure 7 The amorphous nanocatalyst anode of Example 1 is applied to the polarization and power density curves of a direct urea-hydrogen peroxide fuel cell at different temperatures;
[0030] Figure 8 The STEM-EDS result of the atomic ratio of the amorphous nanocatalyst of Example 1;
[0031] Fig. 9 XRF characterization of the amorphous nanocatalyst of Example 1;
[0032] Fig.10 The spectra of the amorphous nanocatalyst of Example 1 and Comparative Example 1 are shown in FIG. Fig.10 (a) Fig.10 (b) In situ IRRAS spectra of urea oxidation on amorphous and crystalline NiWO4 catalysts, respectively. Fig.10 (c) Fig.10 (d) In situ IRRAS spectra of urea self-dissociation at open circuit potential on amorphous and crystalline NiWO4 catalysts, respectively.
[0033] Fig.11 is the spectrum fitting result, where Fig.11 (a) is the spectrum fitting result of the amorphous state of Example 1, Fig.11 (b) is the spectrum fitting result of crystalline NiWO4 of comparative example 1;
[0034] Fig.12 The adsorption configurations of urea and carbon dioxide on amorphous nanocatalysts and crystalline NiWO4;
[0035] Fig.13 is the free energy of adsorption of urea and carbon dioxide on amorphous nanocatalyst and crystalline NiWO4. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0037] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0038] Nickel tungstate (NiWO4) has attracted extensive attention in the fields of photocatalysis, supercapacitors and electrocatalysis due to its stable structure and superior catalytic performance compared to WO3 and NiO.
[0039] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0040] Example 1
[0041] (1) Dissolve 0.005 mol Ni(NO3)2·6H2O and 0.005 mol Na2WO4 in 30 mL of deionized water and stir continuously in a flask to form a light green solution and a colorless solution, respectively;
[0042] (2) adding the Na2WO4 aqueous solution dropwise into the Ni(NO3)2 aqueous solution while stirring to obtain a suspension;
[0043] (3) stirring the suspension for 2 h, and then immersing for 12 h to obtain a precipitate;
[0044] (4) The precipitate was rinsed with a large amount of deionized water to remove the remaining reagent, and then dried in an oven and recorded as a-NiWO4.
[0045] Comparative Example 1
[0046] (1) Dissolve 0.005 mol Ni(NO3)2·6H2O and 0.005 mol Na2WO4 in 30 mL of deionized water and stir continuously in a flask to form a light green solution and a colorless solution, respectively;
[0047] (2) adding the Na2WO4 aqueous solution dropwise into the Ni(NO3)2 aqueous solution while stirring to obtain a suspension;
[0048] (3) The suspension was placed in an autoclave at 180°C and hydrothermaled for 2 h. After the autoclave was naturally cooled to room temperature, the reagent was filtered and separated, washed with distilled water for multiple times, and dried at 70°C for 5 h, which was recorded as c-NiWO4-2h.
[0049] Comparative Example 2
[0050] (1) Dissolve 0.005 mol Ni(NO3)2·6H2O and 0.005 mol Na2WO4 in 30 mL of deionized water and stir continuously in a flask to form a light green solution and a colorless solution, respectively;
[0051] (2) adding the Na2WO4 aqueous solution dropwise into the Ni(NO3)2 aqueous solution while stirring to obtain a suspension;
[0052] (3) The suspension was placed in an autoclave at 180°C and hydrothermaled for 12 h. After the autoclave was naturally cooled to room temperature, the reagent was filtered and separated, washed with distilled water for multiple times, and dried at 70°C for 5 h, which was recorded as c-NiWO4-12h.
[0053] Comparative Example 3
[0054] (1) Dissolve 0.005 mol Ni(NO3)2·6H2O and 0.005 mol Na2WO4 in 30 mL of deionized water and stir continuously in a flask to form a light green solution and a colorless solution, respectively;
[0055] (2) adding the Na2WO4 aqueous solution dropwise into the Ni(NO3)2 aqueous solution while stirring to obtain a suspension;
[0056] (3) The suspension was placed in an autoclave at 180°C and hydrothermal for 24 h. After the autoclave was naturally cooled to room temperature, the reagent was filtered and separated, washed with distilled water for multiple times, and dried at 70°C for 5 h. This was recorded as c-NiWO4-24h.
[0057] The following performance tests were conducted on the NiWO4 nanocatalyst for electrocatalytic oxidation of urea:
[0058] 1. Characterization of material properties:
[0059] See also Figure 1 , Figure 1 The SEM and EDX images of the amorphous nanocatalyst prepared in Example 1 show that the a-NiWO4 catalyst is a uniform spherical nanoparticle with an average particle size of about 150 nm and a relatively narrow distribution. Figure 8 STEM-EDX and Fig. 9 From the XRF diagram, it can be seen that the atomic ratio of Ni, W, and O is 1.1:1:3.9.
[0060] See also Figure 2 , Figure 2 The XRD patterns of the products prepared in Example 1 and Comparative Examples 1-3 are as follows: Figure 1 It can be seen that the c-NiWO4 samples of Comparative Examples 1-3 all have typical diffraction peaks of NiWO4 (JCPDS No.15-0755) after being hydrothermally treated for different time periods, indicating that the c-NiWO4 samples are crystalline. However, the a-NiWO4 sample prepared in Example 1 has no diffraction peaks, indicating that the a-NiWO4 synthesized by the one-step coprecipitation method is amorphous.
[0061] See also Figure 3 , Figure 3 The HRTEM and SAED images of the amorphous nanocatalyst prepared in Example 1 are shown in the inset. No obvious lattice fringes are observed in the HRTEM image, while the SAED pattern has no crystal features and diffraction points, further confirming that the a-NiWO4 synthesized by the one-step coprecipitation method is amorphous. Figure 1-Figure 3 , indicating that the amorphous nanocatalyst was prepared in Example 1.
[0062] 2. Electrochemical test of NiWO4 catalysts of Example 1 and Comparative Examples 1-3:
[0063] In the three-electrode system, the electrochemical performance was tested using carbon rod and Hg / HgO as the counter electrode and reference electrode respectively. The treated catalyst materials were electrochemically tested in 1M KOH solution and 1M KOH + 0.33 M urea respectively. -1 Cyclic voltammetry (CV) measurements were performed between 0 and 0.65 V vs. Hg / HgO at a scan rate of 1.5 %.
[0064] See also Figure 4 , Figure 4The amorphous nanocatalyst of Example 1 and the crystalline NiWO4 electrode of Comparative Example 2 were tested in 1M KOH at 10 mV·s -1 Electrochemical performance diagram at scanning rate, the peaks in each CV are the formation peaks of NiOOH during forward scanning and the formation peaks of Ni(OH)2 during reverse scanning. The peak area of NiOOH formed on the amorphous nanocatalyst nanoparticles of Example 1 is significantly larger than the peak area of crystalline NiWO4 of Comparative Example 2, indicating that more NiOOH active sites can be generated on the amorphous nanocatalyst.
[0065] See also Figure 5 , Figure 5 The amorphous nanocatalyst of Example 1 and the crystalline NiWO4 electrode of Comparative Example 2 were tested in 1M KOH + 0.33M urea at 10 mV·s -1 Electrochemical performance diagram at scanning rate; In comparison, the current density of the hydrothermally treated crystalline NiWO4 and the c-NiWO4-12h catalyst of Comparative Example 2 is very small. In the urea electro-oxidation reaction, the urea electro-oxidation activity of the amorphous nanocatalyst of Example 1 is significantly higher than that of the crystalline NiWO4 catalyst.
[0066] 3. Analysis of catalytic mechanism
[0067] In order to better understand why the catalytic activity of amorphous nanocatalysts is significantly higher than that of crystalline NiWO4, in situ infrared spectroscopy studies were performed. Fig.10 (a) and Fig.10 (b) shows that during the anodic scan of amorphous and crystalline NiWO4, the -1 and 1381cm -1 Two upward peaks were observed at the center, which corresponded to CNO - and CO3 2- , and is consistent with previous IRRAS studies. These two species demonstrate the incomplete conversion of urea (to CNO) on both NiWO4 catalysts. - ) and complete oxidation (to CO2). At the same time, two corresponding urea (1669cm -1 and 1473cm -1 ), indicating its consumption. To further compare the relative ratios of the two oxidation pathways, the spectra collected between 0.55 V and 0.6 V were fitted, see Fig.11 , CO3 2- With CNO - On the amorphous nanocatalyst, CO3 2- and CNO -The integrated area ratio is 1.05, which is much higher than 0.69 of crystalline NiWO4. These results show that the amorphous nanocatalyst is more inclined to completely oxidize urea to CO2 than crystalline NiWO4, and has a higher catalytic efficiency for urea.
[0068] It is worth mentioning that urea can even spontaneously dissociate on the amorphous nanocatalyst at open circuit potential. Fig.10 As shown in the time-resolved IRRAS spectrum in (c), CNO can be clearly observed on the amorphous nanocatalyst within one minute after the working electrode is immersed in the KOH solution containing urea. - and CO3 2- The continuous growth of the band without any potential control was accompanied by the growth of the urea band in the downward direction (consumption). However, no spontaneous dissociation of urea was observed on crystalline NiWO4 ( Fig.10 (d)), which indicates that the amorphous nanocatalyst has a stronger interaction with urea molecules.
[0069] The adsorption behaviors of urea reactant and CO2 product were studied by theoretical calculations, revealing the reasons for the differences in surface activity and selectivity between the two catalysts. Fig.12 The most stable adsorption configurations of urea and carbon dioxide on the surfaces of amorphous nanocatalysts (a-NiWO4) and crystalline NiWO4 (c-NiWO4) are shown. Urea is adsorbed on a-NiWO4 by combining a N atom with an O atom on the surface, while on c-NiWO4, urea is adsorbed by combining an O atom with a Ni atom on the surface. The distance between the urea molecule and the catalyst surface on a-NiWO4 is about On c-NiWO4 is about The closer distance of the urea molecule on a-NiWO4 causes one of its CN bonds to move from (c-NiWO4) is further stretched to like Fig.13 As shown, the adsorption free energy of urea on a-NiWO4 is -1.03 eV, which is much more negative than the adsorption free energy on c-NiWO4 (-0.69 eV).
[0070] These results suggest that the stronger interaction between urea and a-NiWO4 may lead to its self-dissociation, which is consistent with the above-mentioned time-resolved IRRAS measurement results, see Fig.10 (c) and Fig.10(d). In addition, since previous studies have shown that CO2 adsorption is the rate-limiting step in urea electrooxidation, it is of great significance to further study the configuration and energy of CO2 adsorption on the surfaces of the two catalysts. On a-NiWO4, no strong binding between CO2 and the catalyst surface was observed, while on c-NiWO4, CO2 was bound to the Ni atom on the surface through one of its O atoms, as shown in Figure 2. Fig.12 . Not only the distance between a-NiWO4 and CO2 molecules Larger than c-NiWO4 Moreover, the adsorption free energy of CO2 on a-NiWO4 (0.04 eV) is more positive than that on c-NiWO4 (-0.41 eV), see Fig.13 , indicating that the interaction between CO2 and a-NiWO4 is weak.
[0071] Since the desorption of CO2 is likely to be the rate-limiting step in urea electrooxidation, weaker CO2 adsorption will accelerate the overall reaction rate. Since the free energy changes of adsorption and desorption have opposite signs, the negative desorption free energy of CO2 (-0.04 eV) suggests that the desorption of CO2 is spontaneous on a-NiWO4. In addition to improving the overall reaction kinetics, the promoted CO2 desorption on a-NiWO4 can also improve the selectivity of the complete oxidation pathway over the incomplete oxidation pathway, which is consistent with the higher CO3 detected by the in situ IRRAS study. 2- / CNO - The ratio is consistent, see Fig.11 (a) and Fig.11 (b).
[0072] 4. Performance evaluation of fuel cells:
[0073] See also Figure 6 , Figure 6 Figure 1 is a schematic diagram of the structure of a direct urea-hydrogen peroxide fuel cell. It can be seen that on the anode side, the urea solution flows into the anode flow field, then diffuses into the anode NiWO4 catalyst layer, generates electrons thereon and conducts to the cathode through an external circuit. On the cathode side, the hydrogen peroxide solution enters the cathode flow field and is transported to the cathode catalyst layer, where the hydrogen peroxide reacts with the protons and electrons on the Pt catalyst to generate water. At the same time, K + Ions pass through the cation exchange membrane and migrate from the anode to the cathode, closing the internal circuit.
[0074] See also Figure 7 , Figure 7 The amorphous nanocatalyst anode of Example 1 is applied to the polarization and power density curves of the direct urea-hydrogen peroxide fuel cell at different temperatures. Figure 7It can be seen that at 20°C, the open circuit voltage (OCV) of the direct urea-hydrogen peroxide fuel cell is 0.77 V and the peak power density is 0.6 mW·cm -2 When the temperature is increased to 60°C, the performance of the direct urea-hydrogen peroxide fuel cell is further improved, with an OCV of 0.97 V and a peak power density of 1.3 mW·cm -2 , the maximum current density is 7.0 mA·cm -2 .
[0075] The above results show that the amorphous nanocatalyst prepared by the one-step coprecipitation method of the present invention has high urea electro-oxidation activity and is a direct urea fuel cell anode catalyst with great application prospects.
[0076] Example 2
[0077] (1) Dissolve 0.004 mol Ni(NO3)2·6H2O and 0.005 mol Na2WO4 in 30 mL of deionized water and stir continuously in a flask to form a light green solution and a colorless solution, respectively;
[0078] (2) adding the Na2WO4 aqueous solution dropwise into the Ni(NO3)2 aqueous solution while stirring to obtain a suspension;
[0079] (3) stirring the suspension for 1 hour and then immersing for 24 hours to obtain a precipitate;
[0080] (4) The precipitate is rinsed with a large amount of deionized water to remove the remaining reagent, and then dried in an oven to obtain an amorphous nanocatalyst.
[0081] Example 3
[0082] (1) Dissolve 0.005 mol Ni(NO3)2·6H2O and 0.004 mol Na2WO4 in 30 mL of deionized water and stir continuously in a flask to form a light green solution and a colorless solution, respectively;
[0083] (2) adding the Na2WO4 aqueous solution dropwise into the Ni(NO3)2 aqueous solution while stirring to obtain a suspension;
[0084] (3) stirring the suspension for 1.5 h and then immersing for 24 h to obtain a precipitate;
[0085] (4) The precipitate is rinsed with a large amount of deionized water to remove the remaining reagent, and then dried in an oven to obtain an amorphous nanocatalyst.
[0086] Example 4
[0087] (1) Dissolve 0.004 mol Ni(NO3)2·6H2O and 0.004 mol Na2WO4 in deionized water and stir continuously in a flask to form a light green solution and a colorless solution, respectively;
[0088] (2) adding the Na2WO4 aqueous solution dropwise into the Ni(NO3)2 aqueous solution while stirring to obtain a suspension;
[0089] (3) stirring the suspension for 2.5 hours and then immersing for 12 hours to obtain a precipitate;
[0090] (4) The precipitate is rinsed with a large amount of deionized water to remove the remaining reagent, and then dried in an oven to obtain an amorphous nanocatalyst.
[0091] After relevant characterization, the substances obtained in Examples 1 to 4 are amorphous nanocatalysts. When used as anode catalysts of direct urea fuel cells, their catalytic performances are better than those of the NiWO4 crystalline nanocatalysts in Comparative Examples 1-3.
[0092] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing an amorphous nanocatalyst, characterized in that: The following steps are involved: (1) Prepare Ni(NO3)2 aqueous solution and Na2WO4 aqueous solution; (2) Add the Na2WO4 aqueous solution dropwise into the Ni(NO3)2 aqueous solution while stirring to obtain a suspension; (3) continuously stirring the suspension, and then allowing it to stand to obtain a precipitate; (4) washing the precipitate and then drying it to obtain an amorphous nanocatalyst; The amorphous nanocatalyst is applied to electrocatalytic oxidation of urea.
2. The method for preparing the amorphous nanocatalyst according to claim 1, characterized in that: In the Ni(NO3)2 aqueous solution in step (1), 0.004-0.005 mol Ni(NO3)2·6H2O is dissolved in every 30 mL of deionized water.
3. The method for preparing the amorphous nanocatalyst according to claim 1, characterized in that: In the Na2WO4 aqueous solution in step (1), 0.004-0.005 mol Na2WO4 is dissolved in every 30 mL of deionized water.
4. The method for preparing the amorphous nanocatalyst according to claim 1, characterized in that: In step (2), the molar ratio of Ni to W in the suspension is (0.8-1.25):
1.
5. The method for preparing the amorphous nanocatalyst according to claim 1, characterized in that: The drying temperature in step (4) is 70°C.
6. An amorphous nanocatalyst, characterized in that: Obtained according to any one of the preparation methods of claims 1-5.
7. An amorphous nanocatalyst, characterized in that: Nano-spherical.
8. The use of the amorphous nanocatalyst according to claim 7, characterized in that: As anode catalyst in direct urea fuel cells.